The Effectiveness of Ethyl Acetate Extract From Breadfrui (Artocarpus Altilis) Leaves to Inhibit Diarrhea-Causing Bacteria - Yusianti Silviani; Ardy Prian Nirwana (Biomedika, 2021)
Diarrhea is a health problem that commonly occurs in developing countries. Bacteria that cause diarrhea are among others Escherichia coli, Salmonella typhosa and Staphylococcus aureus. This research aimed to investigate the diameters of inhibition zones of breadfruit leaf (A. altilis) ethyl acetate extract in different concentrations against the growth of Escherichia coli, Salmonella typhosa and Staphylococcus aureus. The research applied an experimental laboratory by using a post-test control group design. This research was performed at the Bacteriology Laboratory of STIKES Nasional by using the diffusion disk method. The research showed the radical zone diameters against Escherichia coli with the concentrations of 20%, 40%, 60%, 80%, and 100%, were 6.16 mm, 6.41 mm, 6.74 mm, 7.49 mm, and 7.79 mm, respectively. The inhibition zones against Staphylococcus aureus were 8.15, mm 9.43 mm, 10.29, 10.38 mm and 11.42 mm, while against Salmonella typhosa were 7.94 mm, 8.87 mm, 10.15 mm, 10.26 mm, and 11.23 mm, respectively. The results of the ANOVA test showed the p-value=0.00 and the results of the LSD test revealed the differences in the inhibition effects of A. altilis leaf extract against the growth of E. coli, S. typhosa and S. aureus. This study concludes that concentration variations of Artocarpus altilis leaf ethyl acetate extract can inhibit the growth of Escherichia coli, Staphylococcus aureus, and Salmonella typhosa.